Prinsip-Prinsip Penyelenggaraan Peradilan Menurut Fiqh Qadha dan Undang-Undang di Indonesia - Sucipto, Imam; Mukhlas, Oyo Sunaryo (ISLAMICA, 2022)
This study aims to analyze the legal system adopted in Indonesia. Mix Law System is one of the applicable legal systems, in addition to the enactment of the national legal system applies also Islamic law. The existence of Islamic Law is manifested in the constitution of the State of Indonesia which is commonly known as the 1945 Constitution of the Republic of Indonesia. Where the 1945 Constitution is a basic law that regulates the life of the nation and state in order to realize a just government and a prosperous people. This research uses an empirical sociological approach method that is descriptive analysis with the use of qualitative data as the type of research and library research as one of the data collection techniques. This research concludes that, first: The principles of Islamic Law that are used as the ideal foundation of fiqh are the principle of tauhidullah, the principle of insaniyah, the principle of tasamuh, the principle of ta'awun, the principle of silaturahim bain annas, the principle of justice, and the principle of benefit. As for knowing the theories of Islamic law enforcement in the apostolic period of Muhammad SAW are the theory of confession, the theory of accession, the theory of proof, the theory of verdicts, the theory of oaths, the theory of forgiveness. Second: Dispute resolution based on classical Islamic law namely, Al Sulh (Peace), Tahkim (Arbitration), Wilayat al Qadha (Judicial power). Third: The principles of judicial administration according to fiqh qadha and Indonesian law there is a strong correlation between the state and Islam, including Islamic law which has become a living law in the life of the nation and state. Fourth: The principles in the constitution also have relevance to the principles in Islamic Law which are regulated in the Quran and the Al-Hadith including the principles of justice, equality, and welfare. Based on this, Indonesia, which is based on Pancasila and the 1945 Constitution, can be reviewed from the perspective of Islamic law as an effort to realize the laws regulated in the Quran and Al-Hadith.